The Rise and Decline of the Muslim Ummah: A Historical Study of the Era of Salahuddin Al-Ayyubi's Leadership - Jafrullah, Ruli Jafrullah; Wardana Ritonga, Apri; Nuraini, Ayat; Setiadi, Andri (STAI Publisistik Thawalib Jakarta, 2023)
Studying Islamic history is essential to understanding its rise and decline, including the roles of education, intellectual thought, and leadership, as valuable lessons for Muslims in facing contemporary challenges. The purpose of this study is to explain and describe the rise and decline of the Muslim community. The research was conducted through a literature review, with data sources including articles, books, magazines, and news reports. This qualitative study employed a library research method with data collection techniques based on document analysis. Findings show that the decline of Islamic civilization was caused by internal factors such as the closure of the gate of ijtihad, sectarian conflicts, poverty, and weakening solidarity. External factors like Western imperialism, Zionism, and capitalism further worsened the condition. Meanwhile, Europe’s rise in science and technology was greatly influenced by Islamic civilization, particularly from Muslim Spain. Muslim scholars such as Ibn Rushd and Ibn Sina made significant contributions to the European Renaissance. Salahuddin al-Ayyubi became a symbol of just and wise leadership, bringing Islamic glory through his courage, commitment to justice, and defense of the people. Conclusion: Studying Islamic history has a positive impact on Muslims, especially in strengthening their piety.